ANTIOXIDANT STATUS AND MINERAL LEVELS IN DIABETIC PATIENTS IN NNEWI (Journal of Biomedical Investigation, 2011)
The study was designed to determine the serum levels of antioxidants, mineral levels, antioxidant enzymes and total antioxidant status in diabetic patients, and the control subjects. The plasma levels of antioxidants (albumin, uric acid, total antioxidant status) minerals (magnesium, zinc, selenium and copper) and antioxidant enzyme (superoxide dismutase, glutathione peroxidase and catalase) were estimated in diabetic and control subjects. In the diabetic patients, the mean fasting blood glucose (FBG)(9.374 ±1.166) mmol/L is significantly higher (P